Identity on the Fork: Examining Local Food Consumption Intention within the Context of Social Identity Theory (Third Sector Social Economic Review, 2025)
With the significant impact of globalization, the importance of consumer identities in the literature is increasing; in this context, understanding the relationship between identity and product preference has become a strategic necessity. While globalization transforms individuals' identity perceptions, the impact of this transformation on gastronomic preferences has also sparked curiosity. Accordingly, this study aimed to determine the relationship between individuals' local and global identities and their intention to consume local food. This research examines the impact of consumers' social identities (local and global identities), shaped by the globalization process, on their tendency to prefer local food, based on social identity theory. A quantitative research method was adopted, and a survey form was used to collect data. Data were collected from 264 volunteers living in Istanbul via an online Google form. The collected data were analyzed using SPSS. The findings reveal that local identity has a positive and significant effect on intention to consume local food, while global identity exhibits a negative but statistically insignificant relationship. In conclusion, the study demonstrates that identity is not only a sociological dimension of belonging but also a significant psychological element shaping consumers' gastronomic preferences. Furthermore, social identity theory appears to offer a strong theoretical basis for explaining gastronomic behavior.
Keywords: Social identity theory; local identity; global identity; local food consumption intention; gastronomy